Preliminary taxonomical investigation of soil enchytraeids (Clitellata, Enchytraeidae) from south region of Tibet, China - Lu, Yajing; Xie, Zhicai; Zhang, Junqian (Zootaxa, 2018)
The biodiversity in the Tibetan region is still poorly known, particularly for its soil organisms. Here, we describe eleven enchytraeid species based on several taxonomical surveys in 2015–2016, from some soil localities in south region of the Tibet, China. All are firstly recorded in this region; seven species (Fridericia ratzeli sensu stricto, F. peregrinabunda, F. cusanica, F. bretscheri, Buchholzia sp., Enchytraeus buchholzi and Henlea sp.) are new records for China.